AL-QUR’AN, REALITAS, SAINTISME, DAN PERSOALAN FILSAFAT ILMU: SUATU TINJAUAN RINGKAS - Muhammad Fadhila Azka (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
Assuming that science alone could represent reality and the facts of the proclamation of nature, the materialistic paradigm that originated in the West divorced science from religion and viewed Islamic science as being opposed to relativity and the affirmation of transcendence. This research intends to demonstrate how the Qur'anic construction of reality serves as the foundation for the advancement of Islamic science. This study also highlights several issues brought about by Scientism's haughtiness, as well as by its own justifications and those of Muslim intellectuals. Researchers collected data utilizing descriptive analysis research methodologies from the Koran, hadith, and books using library research as the source. The results of this investigation demonstrate that scientism is an unscientific philosophy that is neither philosophically rational nor scientific. The paper also comes to the conclusion that natural science cannot be the exclusive means of understanding reality from the perspective of Islamic Science philosophy since methodology is intrinsically tied to the levels and diversity of existence as matter or data. According to epistemology, the interaction between the subject's (reviewer) and the object's faculties of science is the science's method and takes place during an intellectual process for the purpose of producing a science